The timing of rights Issues on the Johannesburg Stock Exchange - N. Bhana (South African Journal of Business Management, 1988)
Although a great deal of trading in rights transactions takes place on the various stock exchanges of the world there is a dearth of empirical evidence which might determine an observable trading strategy related to such transactions. The traditional view is that subscription rights to additional Issues of securities will reach their maximum price shortly after the start of trading and then decrease until the end of the subscription period. The results of this investigation into rights Issues of companies listed on the JSE clearly rejects the 'sell the rights early' trading strategy. It is observed that there is a considerable number of rights which reach their peak price in the middle and in the final trading period. Empirical evidence presented in this paper reveals three factors that could be used to predict the market price of rights listed on the JSE. All three factors are highly correlated with the market price of rights. Therefore, an evaluation of an observable trend in these factors could be used to advantage by investors engaged in rights transactions.
Keywords: 650